If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = -3x + -4 Reorder the terms: 18 = -4 + -3x Solving 18 = -4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 18 + 3x = -4 + -3x + 3x Combine like terms: -3x + 3x = 0 18 + 3x = -4 + 0 18 + 3x = -4 Add '-18' to each side of the equation. 18 + -18 + 3x = -4 + -18 Combine like terms: 18 + -18 = 0 0 + 3x = -4 + -18 3x = -4 + -18 Combine like terms: -4 + -18 = -22 3x = -22 Divide each side by '3'. x = -7.333333333 Simplifying x = -7.333333333
| 20x+30+5x+40=570 | | 20x+30+5x+40=574 | | -7-3x=-12 | | 10cos^2x-11cosx-6=0 | | 20x+30+5x+40=576 | | 20x+30+5x+40=581 | | 20x+30+5x+40=582 | | -3=-4-11x | | 20x+30+5x+40=579 | | -6x-1=-14 | | 20x+30+5x+40=580 | | d+32=108 | | 5y-9=13y+7 | | 20x+30+5x+40=600 | | -24x^3-8x^2=0 | | 20x+30+5x+40=700 | | 7=5-3x | | 4/9=x/15 | | 5m=250 | | 20x+30+5x+40=220 | | 12y+35=3 | | 5-2x=-4 | | 3x^2-17x+12=y | | 3/2X+1/2X | | 3x-8x+7=3x-8+11x | | 11=-8x+4 | | 6x-(4x-3)=11 | | -3x+4=-3 | | y=3x^2-24x+46 | | 7=3x+2 | | 9x+1=-4 | | -10=9x-1 |